PEMBINAAN PENDIDIKAN KARAKTER TOLERANSI BERAGAMA SISWA DALAM TOLERANSI BERAGAMA DI SD FRANSISKUS BUKITTINGGI - Putri Romadoni; Mustafa (CV. ADIBA ASIHA AMIRA, 2024)
This research is motivated by the existence of one of the schools that has participants of different religions who are often found in the comparison of the actions of disrespect for each other. Forms of actions that do not respect the comparison, include: Discriminating against friends who have different religions, discriminatory treatment of friends whose religions are different from your own. Next, disturbing and not respecting others who have different religions, As believers we must respect friends who have different religions, and respect the right of everyone to choose their religion. And do not want to be friends and act badly towards friends who have different religions. This research procedure uses a qualitative descriptive research method. The researcher's information collection uses information collection, analyzes information, interprets information, and ends with a conclusion that refers to the analysis of the information. The information analysis method used is mostly explanatory in nature from the results of questions and answers and selection research. The information that has been obtained will be analyzed qualitatively and described in descriptive form. The results of this study prove that the development of religious personality education of students at SD Fransiskus Bukittinggi. Intended to recognize how a teacher in cheerful religious character of students at SD Fransiskus Bukittinggi. Teachers of religious personality education of students at SD Fransiskus Bukittinggi must be tried and implemented so that the personality of students can be built and fostered from an early age so that when they grow up tomorrow ethics to respect religious comparisons When they associate with the community. And the development of religious personality education of students at SD Fransiskus Bukittinggi so that they can maximize the activities available at SD Fransiskus Bukittinggi and then always carry out tasks that are in accordance with the program located at SD Fransiskus Bukittinggi to cheer up the personality of students in a religious way and glorify comparisons in religion.